Teoría de la propiedad intelectual. Fundamentos en la filosofía, el derecho y la economía. (2015)
Intellectual property as any branch of law has several dimensions. Two traditional are: practical and theoretical. In the first patents are granted or registration certificates of works are requested, among many other procedures where no doubt there are ambiguities that deserve clarification. In the second the fundamentals are analyzed and criticized in search of articulation without adherence to procedural questions. However, after a review of the expert literature, we find that the latter dimension of intellectual property (IP) has little literature. This article analyzes and articulates the most important foundations available in philosophy, law and economics on IP, helping to consolidate the theoretical dimension on the subject.